Diarrhea Prevalence in East Java, Indonesia: Does Access to Sanitation and Health Behavior Ecologically Related? - Hario Megatsari; Agung Dwi Laksono; Anita Dewi Moelyaningrum (Institute of Medico-legal Publications Pvt Ltd, 2021)
Diarrhea is still a problem in East Java in Indonesia. The study aims to analyze the ecological relationshipbetween sanitation access and health behavior with diarrhea prevalence in East Java, Indonesia.The researchconducted the ecological analysis using secondary data from the Ministry of Health of the Republic ofIndonesia report in 2018. The study takes all regencies/cities in East Java Provinces as samples. Apart fromthe diarrhea prevalence in children underfive, four other variables analyzed as independent variables wereaccess and clean water sources, the percentage of coverage of access to healthy latrines, the proportionof proper handwashing behavior, and the proportion of defecating behavior in healthy latrines.The studyanalyzed data using a scatter plot.The study results found that the higher the percentage of coverage ofaccess and clean water source in regency/city, the lower the prevalence of diarrhea in children under five inthat regency/city. The higher the percentage of access to healthy latrines in a region, the lower the majorityof diarrhea in children under five.Meanwhile, the higher the proper handwashing behavior proportion inan area, the lower the prevalence of diarrhea in children under five in that area. Moreover, the higher theproportion of defecating behavior in healthy latrines in a region, the lower the prevalence of diarrhea inchildren under five. The study concluded that sanitation access and health behavior were related to thediarrhea prevalence in children underfive.